Ordinary glass spheres as an alternative injectable material for endoscopic correction of vesicoureteral reflux - YÜCEL, SELÇUK (ELSEVIER SCIENCE INC, 2004)
Purpose: Although they are therapeutically effective, injectable materials for urinary tract are associated with various disadvantages, precluding their universal acceptance. In this study we investigated glass spheres (GSs) as an alternative injectable substance to correct vesicoureteral. reflux (VUR) in an animal model. Materials and Methods: We used 150 to 300 mu GSs suspended in agarose gel to form the injection paste. GS paste was injected into the rectus muscle and submucosa of the bladder in 8 adult New Zealand male rabbits. As a control group, vehicle only was injected into 4 rabbits. The rabbits were sacrificed to harvest the bladder, pelvic lymph nodes, kidney, liver, brain, spleen and lung at month 1 and year 1 of injection. A VUR model was then created by unroofing the 2 ureteral orifices of 12 adult sheep. GS paste was injected into the right subureter and vehicle only was injected into the left subureter. Cystourethrographies were performed at month 3 and year 1 of injection. The sheep were sacrificed at cystourethrography to harvest the bladder, lymph nodes, kidney, liver, brain, spleen and lung. Results: At month 3 and year 1 of injection into rabbit tissues nodule formation was stable in position and volume. Histopathological studies of local and distant organs of the rabbit did not show any granuloma formation or migration of GS. GS paste injection corrected VUR in sheep. Re-injection of GS into still refluxing left units corrected VUR. Local and distant organs, harvested from sheep did not demonstrate distant migration. Conclusions: When injected into bladder submucosa and rectus muscle, GS appears to be inert, biocompatible and efficient. Similarly it is effective for correcting VUR in an animal model. We present our data on GS, encouraging further investigation to develop an alternative injectable material for endoscopic VUR correction.
Keywords: urethra; vesico-ureteral reflux; glass; rabbits; sheep; INJECTION; EXPERIENCE; MIGRATION; BLADDER; POLYTEF; TISSUE; TEFLON; MODEL; ACID